Worringer, Dewey, Goodman, and the Concept of Aesthetic Experience: A Biological Perspective (Itinera, 2022)
The purpose of this essay is to advocate the ideas of Wilhelm Worringer, John Dewey, and Nelson Goodman on the roles of perception, empathy, emotion, and enjoyment in aesthetic experience. I will attempt to do this by offering a novel interpretation of some of these thinkers’ insights from a biological perspective. To this end, I will consider the following questions. What is an aesthetic experience? Does such a thing exist at all? If yes, is there a correlation between the concept of the aesthetic and perception? Is it possible, then, to find a biological basis for aesthetic experience? My argument is that a fresh analysis of the aesthetics of Worringer, Dewey, and Goodman, in light of some of the discoveries and theories of the cognitive neurosciences – such as the biological correlations of emotions, the “as-if-body-loop” theory, the discovery of mirror neurons, and the phenomenon of embodied simulation – may provide a contribution to longstanding philosophical problems relating to the nature of aesthetic experience.